Communication—Scanning Electrochemical Microscopy Analysis of Interleukin-6 in Oral Cancer. (21st October 2020) - Lin, Yen-Tzu; Preet, Anant; Chiu, Yi-Pin; Yip, Bak-Sau; Girault, Hubert H.; Darvishi, Sorour; Wang, Ligang; Lin, Tzu-En
Abstract : Scanning electrochemical microscopy (SECM) offers a highly sensitive and convenient approach for electrochemical mapping of interleukin-6 (IL-6), an oral cancer protein biomarker. In this study, we utilized the SECM to map the distribution of IL-6 for imaging different cancer stages on the tissue sections. The SECM results indicated that IL-6 was expressed higher in cancer tissues as compared to normal tissue and hence, SECM can be employed to improve oral cancer diagnosis. Also, IL-6 analysis can be beneficial for predicting the severity of COVID-19 at an early stage to eliminate the potential risks of serious respiratory complications in affected patients.